2018
DOI: 10.3892/mco.2018.1680
|View full text |Cite
|
Sign up to set email alerts
|

Preponderance of endometrial carcinoma in elderly patients

Abstract: Elderly patients with endometrial carcinoma (EMC) are considered to have a poor clinical outcome. The present study included 79 patients aged ≥70 years with EMC stage I or II according to the International Federation of Gynecology and Obstetrics classification, and it was conducted to analyse the clinicopathological significance of histological type (I or II), depth of myometrial invasion (<1/2 or ≥1/2), lymphovascular invasion (+ or -) and immunohistochemical profile. The aim of these analyses was to determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Endometrial cancer (EC) is one of the common malignant genital tumors in female characterized by high recurrence and adverse outcomes. Its morbidity and mortality have presented an ascending trend in the last few years, and it is reported that it occurs over a wide range of age groups from young individuals to elderly women 1,2. Surgery, chemotherapy, and radiotherapy have been considered as effective treatments for EC 3,4.…”
Section: Introductionmentioning
confidence: 99%
“…Endometrial cancer (EC) is one of the common malignant genital tumors in female characterized by high recurrence and adverse outcomes. Its morbidity and mortality have presented an ascending trend in the last few years, and it is reported that it occurs over a wide range of age groups from young individuals to elderly women 1,2. Surgery, chemotherapy, and radiotherapy have been considered as effective treatments for EC 3,4.…”
Section: Introductionmentioning
confidence: 99%
“…13 Furthermore, Ogane et al reported that ER-negative/p53-positive status is independently associated with a poor prognosis in elderly people with endometrial cancer. 27 However, these studies also differed from ours in that G3 endometrioid carcinoma and other high-grade adenocarcinomas were included in their analyses of the prognostic significance of age and aberrant p53 expression. Moreover, Yano et al reported that the prognosis of G1 endometrioid carcinoma in the elderly with aberrant p53 expression is equivalent to that of conventional G3 endometrioid carcinoma.…”
Section: Discussionmentioning
confidence: 77%
“…In the in vitro study, we found that 5b could inhibit cell proliferation and induce apoptosis in HCT116 cells. Ki-67 and cleaved caspase-3 (CC3) are excellent markers of proliferating and apoptotic cells, respectively (Ogane et al, 2018). To detect the effect of 5b on Ki-67 and CC3 in the tumor tissues, immunohistochemical analysis was performed using anti-Ki-67 and anti-CC3 monoclonal antibodies.…”
Section: Immunohistochemical Analysismentioning
confidence: 99%